Breaking The Cycle Of Intergenerational Child Maltreatment: A Case For Active Efforts For Dependent Minor Parents And Their Children In State Custody. (September 2016) - Hirst, Eliza M.; Jones, Annika L.
Abstract: Dependent minor parents placed in foster care with their children often face significant hurdles. These parents are responsible to make caregiving decisions for their children, while they themselves fall under the caregiving responsibility of the state child welfare system. As such, dependent minor parents live in a "twilight zone" – they hold full parental rights, but limited rights as teenagers. For a number of reasons, the children of minor parents in foster care often come into state custody. When two generations are in foster care at the same time, states must balance the safety and best interests of the children with the rights of minor parents to care for their own children. Currently, the state child welfare system is only required to provide "reasonable efforts" to reunify parents with children when they have been removed from their care for abuse, neglect, or dependency. However, dependent minor parents in state custody often require more supportive services in order to successfully reunify with their children than in a typical child welfare case. This article places the circumstance just described in the context of dependent minor parents' constitutionally protected rights, and advocates for a higher standard which would require states to provide "active efforts" to protect and preserve these young families.